Design and the creation of value - Heskett, John (Bloomsbury Academic, 2017)
"John Heskett was a leading design historian with a particular interest in design and economics. This book publishes for the first time his writings on design and economic value, and design's role in creating value in organisations and products. The first part of Heskett's text introduces the main traditions of economic thought as they explain the relationship between producers, markets, products and consumers; he then goes on to consider the importance of design and design thinking in innovating and creating value in business practice and product development. Heskett refers to examples of businesses such as Dyson and Apple that have successfully responded to the value of design in their practice, and others such as the Ford Motor Company that were faced with the threat of bankruptcy because they failed to encourage innovation and creativity or to respond adequately to the challenges and opportunities presented by new technology. Heskett's text is accompanied by critical and contextualising overviews by leading design scholars, which place Heskett's writings within the framework of contemporary design and business thought and practice"- Resumé vydavatel
Keywords: design; průmyslový design; ekonomické teorie; industrial design; economics (theory); elektronické knihy; monografie; electronic books; monographs